PENGEMBANGAN MEDIA EDU-GAME BERBASIS ANDROID UNTUK MATERI KETERAMPILAN HAND TOOLS, POWER TOOLS, DAN SPECIAL SERVICE TOOLS OTOMOTIF - Faizin, Muhammad; Wijaya, M. Burhan Rubai (Automotive Science and Education Journal, 2020)
The purpose of this research was to develop an android-based Edu-Game learning media, to find out the feasibility, test the relationship with an increase in students' understanding of skills and the practicality of the media. The Edu-Game development model used the 4D development of this model consisting of 4 stages, namely: 1) Define, 3) Design, 4) Development, and 4) Desiminite. The limited scale trial results obtained by increasing student learning outcomes in the psychomotor domain were obtained from the pretest and posttest values. The average yield increase is 15.5. The t-test calculation results obtained thitung = 14.35 while t-table (0.975) (29) = 2.040 at a = 5% with dk = 30-1 = 29, so it can be concluded that there is an increase in the value of students between the pretest and posttest using Edu -Game. The practicality test for Edu-Game products for hand tools, power tools, and special service tools obtained a percentage and final results of 89.7%, so that it can be stated that the products fall into the "very good" category